PASSION FOR SCIENCE AS THE DRIVING FORCE BEHIND SUCCESS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 27 March 2016 – A passion for science has driven Professor Dr. Lee Chow Yang, 47, to succeed in his career to become among the youngest appointed full professor in Universiti Sains Malaysia (USM).